Colonialism, slavery and 'The Great Experiment': Carbon, nitrogen and oxygen isotope analysis of Le Morne and Bois Marchand cemeteries, Mauritius. (June 2020) - Lightfoot, Emma; Čaval, Saša; Calaon, Diego; Appleby, Jo; Santana, Jonathan; Cianciosi, Alessandra; Fregel, Rosa; Seetah, Krish
Highlights: Isotopic analyses of two 19th century cemeteries give insights into Mauritian diets. A wide range of diets was consumed, particularly in terms of C4 consumption. People buried at Le Morne consumed more C4 foods than those at Bois Marchand. The individuals from Le Morne had different childhood diets but similar adult diets. This is consistent with Le Morne's interpretation as a post-emancipation cemetery. Abstract: Slavery, colonialism and emancipation are important aspects of archaeological research in the Atlantic region, but the lifeways of colonial populations remain understudied in the Indian Ocean World. Here, we help to redress this imbalance by undertaking stable isotope analysis (C, N and O) on human remains from Mauritius, a location which played an important role in the movement of people across the Indian Ocean and beyond. The results indicate that a wide range of diets was consumed in Mauritius during the nineteenth century, varying with location and circumstances of birth such that while a range of resources would have been available on the island, the proportions of the different resources consumed was different for different people. Most people consumed some C4 resources, likely maize, although the proportion of the diet that this represented varied widely. There is some evidence for the use of marine resources, with one individual consuming a very high proportion of marine foods. In general, the people buried at the post-emancipation cemetery Le Morne consumed a higher proportion of C4 foodstuffs and a lower proportion of animal protein and/or marine resources than those individuals buried at the formal public cemetery Bois Marchand. The data from La Morne are consistent with a population that lived separately as children and then came to live, and eat, together during adulthood. This study has shown a much more nuanced picture of diet in Mauritius at this time than was previously known. The research complements and enriches the historic narrative, adding dimensions to small islands that would otherwise remain obscure in the absence of rigorous scientific assessment of archaeological finds.